Umrüstung von Güterwagen auf Rollgeräusch-reduzierende Bremstechniken bis zum Fahrplanwechsel 2020/2021. - Brammer, Henning (Springer-VDI-Verl., 2020)
Der Artikel betrachtet den Fortschritt der Umrüstung der Bremsklotzsohlen im Schienengüterverkehr. Die Maßnahmen zur Migration der Technologie in den Markt werden beschrieben. Ergebnisse der Evaluierung des Standes der Umrüstung wie auch Umrüstzahlen auf Basis des nationalen Fahrzeugregisters sowie erste Erkenntnisse aus dem vom BMVI initiierten und vom Eisenbahn-Bundesamt durchgeführten Lärm-Monitoring zur Entwicklung der Schallemissionen von Güterwagen werden präsentiert.

The rolling noise of freight wagons is the dominant noise source in rail traffic. By using composite brake blocks instead of cast iron brake blocks, the wheel is roughened less and the rolling noise is reduced by about 10 dB. A reduction of the rolling noise of freight wagons leads to a comprehensive noise reduction along all lines affected by rail freight traffic noise. On the occasion of the ban on the operation of noisy freight wagons on the German rail network, which will come into effect from 13.12.2020, this article examines the progress made in retrofitting of brake blocks since the approval of composite brake blocks in rail freight traffic. The measures to migrate the technology to the market are described. A result of the evaluation of the status of retrofitting as well as retrofitting figures based on the national vehicle register and first results of the noise monitoring initiated by the BMVI and carried out by the Federal Railway Authority on the development of noise emissions from freight wagons are presented.
Keywords: Schienengüterverkehr; Schienenverkehrslärm; Lärmminderung; Monitoring